Indonesia's Energy Transition Policy in the Perspective of Political Economy Under Geopolitical Risk - Cahayani, Ica; Nurlaela, Della; Nibal, Rachel Kamilia Faradiba (SIYAR Journal, 2026)
This study discusses Indonesia's energy transition policy amid geopolitical risks and global economic and political instability based on the perspectives of energy economics, power structures, economic dependence, and trade wars. Energy transition is proposed due to its increasing popularity as Indonesia promotes clean energy and aims to achieve net zero emissions by 2060 amid geopolitical issues and global economic and political instability. The selection of Indonesia's energy transition policy is to determine the significance and urgency of this policy from an economic policy perspective. This study analyzes Indonesia's energy transition policy from an economic policy perspective through the dimensions of power structures, economic dependence, and trade wars. This study uses a narrative literature review and adopts a research design to extract research data. The data comes from a review of relevant literature found based on predetermined keywords on the topic of the development of Indonesia's energy transition policy. Indonesia's energy transition policy amid the risk of geopolitical instability shows a dynamic that continues to change depending on geopolitical conditions, the international power structure, and ongoing trade wars. This study proves that the energy transition policy is driven by the Indonesian government's commitment to become an zero emission country. The international push for energy transition has an external influence on Indonesia's energy transition policy-making. In its energy transition policy, the Indonesian government faces a major dilemma, structural power challenges, economic/funding dependence, and the existence of national fossil fuels that frame the energy transition policy.